Pengaruh Kebijakan Pendanaan, Deviden dan Profitabilitas Perusahaan terhadap Set Kesempatan Investasi (IOS) - Akhmad Adi Saputro; Lela Hindasah (Universitas Muhammadiyah Yogyakarta, Indonesia, 2007)
The objective this research is to examine financing policy, dividend policy and profitability of the firm association investment opportunity set. The sample of this study consist of 28 firm in Jakarta Stock Exchange period 1999-2004. Common factor analysis is conducted to constructcomposite measures then ranked to classify the growth of sampling firm. To examine the impact of the financing policy, dividend policy, and profitability to the investment opportunity set of the high and low growth firm is used logit regression analysis. The result indicates that the impact between financing policy, proxied by Book value of debt to equity, Market value of debt to equity to investment opportunity set, is significantly negative. The impact between dividend policy proxied by dividend yield and investment opportunity set is significantly negative, but dividen pay out ratio is not significant. The impact of profitability, proxied by return on assets to investment opportunity set is significantly positive.